The imbalance in brand management - Idrobo, Carlos Javier; Institución Universitaria Colegio Mayor del Cauca (Universidad Católica de Pereira, 2017)
This paper presents the importance of keeping a balance in brand management, with the main objective to ease an emotional relationship with the target audience. Starting from small mistakes or omissions in the image approach, organizations can substantially turn aside the way of a better relationship with the user. In order to avoid this situation, the brand management should not be based solely on figures or in a purely aesthetic issue, it must maintain a stable balance between the institutional reality and the personality it projects. The brands must fulfil the promise they make to their users. A study case focus in the Institución Universitaria Colegio Mayor del Cauca brand, located in Popayán city, Cauca, is presented.